TINJAUAN KETIDAKLENGKAPAN PENGISIAN AUTENTIFIKASI DOKTER PADA FORMULIR RINGKASAN PASIEN PULANG DI INSTALASI REKAM MEDIS PASIEN RAWAT INAP RUMAH SAKIT UMUM PINDAD BANDUNG - Intan Pujilestari; Neni Rohaeni (UPPM Politeknik TEDC Bandung, 2019)
Incomplete medical resume is a problem because medical resumes can provide detailed information about what has happened while the patient was hospitalized so that it has an impact on the quality of medical records and services provided by the hospital. Based on a preliminary study from February 8 to March 8, 2021, the authors found that the number of medical records on the summary form of discharged patients at the inpatient medical record installation were incomplete, such as the signature and full name of the doctor that were not filled out, out of 225 medical record files in the form summary of patients returning home, only 155 forms were completed and 70 forms were incomplete. This study aims to determine the incomplete description of filling in the doctor's authentication on the summary form of discharge patients at the medical record installation of inpatients at the Pindad General Hospital, Bandung.The research method used is descriptive research method. Data collection techniques in research include: observation, interviews, documentation and literature study.Based on research at the Pindad General Hospital, Bandung already has a Standard Operating Procedure, but in its implementation it has not been in accordance with the standards set by the hospital. The results showed that the incomplete completion of authentication on the discharge patient summary form carried out by the author obtained a percentage of the completeness of the discharge patient summary form filling of 73.2% and the incomplete filling of 26.8% from October and November with a total sample of 87 discharge patient summary forms.